Women in Malayalam Cinema : naturalising gender hierarchies - Meena,Pillai.T Ed.; Pillai, Meena T. (New Delhi : Orient BlackSwan, 2010)
Contributed articles.
pt. 1. Introduction -- pt. 2. Historical mappings of gender -- pt. 3. Representing women? the sexual contract -- pt. 4. Contemporary crossings : foiled promises.
Includes bibliographical references (p. [221]-228) and indexes.
Keywords: Motion pictures -- India -- Kerala; Women in motion pictures